2022
DOI: 10.1037/fam0000954
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating the study of familism across racial/ethnic groups: Creation of the Short Attitudinal Familism Scale.

Abstract: As the research on familism values, or cultural values relating to support, interconnectedness, and obligations has blossomed, scholars are increasingly interested in the applicability and impact of familism values across diverse racial/ethnic youth. However, existing measures of familism tend to be long, posing potential practicality issues and have not been validated for use across youth from different racial/ethnic groups. Through a series of conceptual steps and exploratory and confirmatory factor analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
(136 reference statements)
1
12
0
Order By: Relevance
“…This suggests that family orientation could be an effective target for clinical interventions seeking to promote children’s self-regulation. Furthermore, consistent with our hypotheses and previous research (Christophe & Stein, 2022), associations with children’s self-regulation were similar across racial/ethnic groups. Although researchers posit that valuing and prioritizing the family is a universal, rather than specific, cultural practice (Hardway & Fuligni, 2006), these findings do not minimize the importance of familism for racial/ethnic minority groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that family orientation could be an effective target for clinical interventions seeking to promote children’s self-regulation. Furthermore, consistent with our hypotheses and previous research (Christophe & Stein, 2022), associations with children’s self-regulation were similar across racial/ethnic groups. Although researchers posit that valuing and prioritizing the family is a universal, rather than specific, cultural practice (Hardway & Fuligni, 2006), these findings do not minimize the importance of familism for racial/ethnic minority groups.…”
Section: Discussionsupporting
confidence: 91%
“…Several attitudinal and behavioral measures of familism exist, with most childhood research relying on parent reports (see Stein et al, 2014). Familism is argued to be specific to Hispanic/Latino individuals (Grau et al, 2009) but has also been identified in other racial/ethnic groups (Christophe & Stein, 2022). We use the term familism when describing previous research and family orientation in our study given the racial/ethnic diversity of our sample.…”
Section: Family Orientation As a Cultural Process In Childhoodmentioning
confidence: 99%
“…In the present study, the notion of familism ( family values) is understood as a central culture value related to family support, loyalty, strong, positive family bonds and the sense of obligation towards the family (Christophe et al, 2022). It has been assumed that familism includes five dimensions: respect, family support, religion, material success and achievements and individualism.…”
Section: Family Valuesmentioning
confidence: 99%
“…Familism (familismo) refers to the family as a central cultural value and most of the time case studies discuss immigrant social groups with Latinx or Asian cultural background (e.g., Choi et al, 2021;Hernández & Bámaca-Colbert, 2016). Most research highlights the positive effects of the familistic attitudes and behaviors of immigrant Latinx and Asian youth, such as stronger resilience to discrimination (for an overview, see Christophe & Stein, 2022). However, recent publications also draw attention to the limits of strong familist attitudes, especially its ambivalent or even negative relation to family members who identify with the LGBTQ+ community (Patrón, 2021).…”
Section: Introductionmentioning
confidence: 99%